Calculation and measurement of ampacity for class 5 flexible aluminum cable at 110 °C - Fernando Esma Agustin; Akhtar Kalam; Aladin Zayegh (Institute of Advanced Engineering and Science, 2021)
Class 5 flexible aluminum conductors are not common in cable manufacturing industry due to insufficient study on cable joints and connectors. The table of ampacities for aluminum conductors at 110 °C in AS/NZS3008.1.1 standards are also not available as a reference guide for electrical system designers that restricts the installation of aluminum low voltage (LV) cabling system to operate at 90 °C of conductor maximum operating temperature where 110 °C cables are permitted in Australia. In this paper, the cable ampacities of various LV Class 5 flexible aluminum cables at maximum operating temperature of 110 °C are calculated using IEC60287 and AS/NZ3008.1.1 standards. The calculated ampacities from the formula presented in clause 4.4. of AS/NZS3008.1.1 are verified by using the 6kA inductive current generator to determine the suitability for use. The joint temperature between cable and shear bolt mechanical connectors are simultaneoulsy simulated using the calculated ampacities to determine the suitability of mechanical shear bolt connectors when the coefficient of thermal expansion of material is considered. The observed differences between the calculated and measured values demonstrate the relevance of formula used in determining the current ampacity at 110 °C conductor temperature in free air.